Serum Lipoprotein Level In Subjects With Ischemic Heart Disease Carrying Single Nucleotide Polymorphism Rs6415084 Of LPA Gene - Kulkarni, Vineet; Shettya, Sukanya; Chakraborty, Anirban; Subramanyam; Patil, Prakash; Bhandary, Roopa (Indian journal of clinical biochemistry, 2022)
Severity of Ischemic Heart disease was determined by SYNTAX score. SNP genotyping assay among IHD subjects was performed by Real time PCR method by using Taqman genotyping assay kit. Results- The Median Lp(a) level of all subjects was 15.2mg/dF (7.3-26.7) Severe subjects had higher Median Lp(a) level(18.9mg/dF (12.3-24.4) compared to mild subjects (13.7mg/dL(6.6-18.6). Out of 100 study subjects, 38 subjects had C/T genotype, 17 had CC genotype 15 had TT genotype and 30 subjects did not carry any genotype (undetermined). Subjects carrying TT genotype had a slightly higher median Lp(a) level[22.6mg/dF(11.1-45.3)] compared to subjects carrying CC [19.4mg/dF(17-31.2)]and CT genotype[20.05(11.3-28.9)]. Conclusion- Severe subjects had higher Lp(a) level compared to mild subjects. There was no significant correlation between Lp(a) and SYNTAX score among severe group. Positive correlation between Lp(a) and SYNTAX score was observed only among female mild group. Subjects carrying homozygous allele(TT) had slightly higher median Lp(a) level compared to subjects carrying heterozygous(CT) population.